ANALISIS PEMASARAN SUSU SAPI PERAH DI KABUPATEN BOYOLALI (MILK MARKETING ANALYSIS IN BOYOLALI DISTRICT) - Setyowati, Setyowati (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2008)
The research aims to (1) discover the marketing network of milk in Boyolali District, (2) analyse the margin, cost, and profit of marketing at the marketing institution level in Boyolali (3) analyse the efficiency of milk marketing from the economic point of view in Boyolali. Using descriptive method, the research was undertaken in Musuk Sub-District, Boyolali. Through proportional random sampling, 19 farmers from Sukorejo Village and 11 farmers from Karanganyar Village have been selected, while trader samples were selected through snowball sampling. The result of research proved that there are two types of milk marketing network as follows: Type I: Farmer - KUD Musuk (Village Level Cooperative) - GKSI - Consumer (IPS); Type II: Farmer - KUD Musuk - Middleman Consumer. The Type I network is more commonly applied as for 19 farmers used such network, while Type II was only applied by 11 farmers. The marketing cost in Type I was Rp. 371,66 per liter and in Type II was Rp. 998,63 per liter. The profit for Type I was Rp 128,34 per liter and Rp. 451.37 per liter for Type II. The marketing margin for Type I was 24.39% as for Type II was 48.33%. Farmers share of Type I was 76% and for Type II was 52%. Type I was more efficient than Type II for having a lower marketing margin (24.39%<48.33%) and higher value of farmers share (76%>52%).